Alturas de corte e adição de inoculante para ensilagem de milho - Müller, Sayonara Salvatti (2019)
Preserved fodder is used to feed lactating cows both in the pasture system and in the stall systems. The objective of this study was to evaluate the effect of different cutting heights (20, 40 and 60 cm) of corn plants for silage with or without microbial additive on the qualitative aspects of silage. The experimental design was completely randomized, with treatments in factorial arrangement (three cutting heights and two inclusion levels of microbial additive), using ten replicates. An area of 1.0 ha sown (75,000 plants ha-1) with glyphosate tolerant corn hybrid will be used. Corn was harvested when the grain reached the farinaceous-hard point. For each height the plants of five sites (2 linear m) were randomly established within the experimental area, excluding the edges (3 rows or 2.00 m). After the crushing of the material, for each height of cut, two mounds of green fodder of 15.00 kg each were formed. Five samples per plot were collected to evaluate forage characteristics prior to silage. After that, the solution with the microbial additive SIL-ALL(marca registra) 4x4 was added to a pile of forage of each height. Minisil were made in plastic bags (20 microns) with capacity for 2.00 kg of forage. The establishment of anaerobiosis and sealing were performed with the aid of an Industrial Vacuum Packing Machine. For each treatment, 10 minisil were made. After 60 days the minisil was opened. The forage contained in six minisilos was destined for laboratory analyzes. The remaining minisil (four) were used to determine aerobic stability. The dry matter, pH, electrical conductivity, water activity and dry matter losses were determined in the samples of these minisilos as well as in the forage samples before ensiling.